Development of Novel Magnesium Alloys with Alkaline Earth Metal Oxides - Shae K. Kim (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
The aim of this study is to manufacture magnesium alloys with alkaline earth metal oxides (BeO, CaO, MgO or SrO) additions with the objectives of (1) ensuring safety during processing and applications by raising the ignition temperature and reducing oxidation, (2) protecting the environment by reducing or eliminating use of protective gases, (3) maintaining or improving elevated temperature properties with lower amount of Ca or Sr or rare earth metals when compared with conventionally developed high-temperature magnesium alloys, (4) developing cleaner strip casting and continuous casting processes without hot tearing and (5) obtaining all of these objectives without sacrificing mechanical properties or increasing the cost of magnesium alloys.